The role of parents in educating children on the values of religious moderation in the digital era - Muchamad Rynaldi Cahyo; Muhammad Syakur; M. Jamal; Muh. Baehaqi; Sumarjoko; Husna Nashihina (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2024)
The digital era poses unprecedented challenges to family resilience, particularly concerning the rapid and often unfiltered flow of religious information that potentially triggers intolerant attitudes and radicalization among the younger generation. This study aims to analyze the strategic role of parents in educating children on religious moderation values (wasathiyah) amidst the rising phenomenon of cyber-religion. Using a descriptive qualitative approach, data were collected through in-depth interviews, observations, and documentation focusing on urban Muslim families who actively engage with digital media. The findings indicate that the parental role has undergone a significant transformation from traditional educators to digital gatekeepers and providers of digital modeling. Parents internalize four foundational pillars of moderation: tolerance (tasamuh), non-violence, balance (tawazun), and an accommodative stance toward local culture. These mentoring strategies are implemented through dialogic, two-way communication rather than one-way instructions, alongside the reinforcement of the Tabayyun (information verification) principle as a crucial basis for Islamic digital literacy. However, this study also identifies a critical digital gap—a competence disparity between generations—that creates an